Analysis on the categorization of conservation status of orchids in Peru:: the case of the genus Telipogon - Martel, Carlos (2020)
The orchid family is one of the plant groups with the highest number of species included in conservation lists worldwide. However, this number is still small considering the high orchid diversity and vulnerability. This is particularly manifest in Peruvian lists of threatened flora. In this comment, I analyse their representativeness in conservation lists in Peru, with an emphasis on species of the genus Telipogon. My analysis highlights the importance of elaborating accurate lists, consistent with the Aichi Biodiversity Targets of the Strategic Plan for Biological Diversity 2011-2020.